Political writings - Dreiser, Theodore, 1871-1945 (Dreiser, Theodore, 1871-1945. Works. 1988., 2011)
Synopsis: Theodore Dreiser staked his reputation on fearless expression in his fiction, but he never was more outspoken than when writing about American politics, which he did prolifically. Although he is remembered primarily as a novelist, the majority of his twenty-seven books were nonfiction treatises. To Dreiser, everything was political. His sense for the hype and hypocrisies of politics took shape in reasoned but emphatic ruminations in his fiction and nonfiction on the hopes and disappointments of democracy, the temptations of nationalism and communism, the threat and trumpets of war, and the role of writers in resisting and advancing political ideas. Spanning a period of American history from the Progressive Era to the advent of the Cold War, this generous volume collects Dreiser's most important political writings from his journalism, broadsides, speeches, private papers, and long out-of-print nonfiction books. Touching on the Great Depression, the New Deal, and both World Wars as well as Soviet Russia and the persecution of Jews in Nazi Germany, these writings exemplify Dreiser's candor and his penchant for championing the defenseless and railing against corruption. Positing Dreiser as an essential public intellectual who addressed the most important issues of the first half of the twentieth century, these writings also navigate historical terrain with prescient observations on topics such as religion, civil rights, national responsibility, individual ethics, global relations, and censorship that remain particularly relevant to a contemporary audience. Editor Jude Davies provides historical commentaries that frame these selections in the context of his other writings, particularly his novels.